Representing the Mother's Role in the YouTube Ad: A Roland Barthes Semiotic Analysis of 'Mother's Amazing Hands’ - Muhamad Yusuf Alfauzi; Oktaviana Purnamasari (Dialogika : Jurnal Penelitian Komunikasi dan Sosialisasi, 2025)
In advertising, females are frequently positioned as the center of attention to establish product image through culturally recognized signs and symbols. Advertisements transcend their promotional function, acting as media that both reflect and influence societal perceptions, including gender roles within daily life. This is exemplified in the Vicks VapoRub advertisement titled "Mother's Amazing Hands," which portrays women as mothers perpetually prepared to care for their families. This study investigates the representation of the mother's role within the aforementioned advertisement using Roland Barthes' semiotic theory. The research aims to twofold: 1) identify the denotative, connotative, and mythical meanings embedded within the Vicks VapoRub "Mother's Amazing Hands" ad; and 2) analyze the portrayal of the mother figure through the lens of Barthes' semiotic framework. The research employed a qualitative descriptive approach, utilizing Barthes' semiotic analysis method alongside concepts of social construction of reality, cinematography techniques, and the societal role of mothers. Through the analysis of verbal, non-verbal, audio, and visual elements within the advertisement, the study revealed the multifaceted representation of the mother's role. This includes functions of caregiving, nurturing, and treatment of family members, ultimately portraying the tangible actions a mother takes in providing for her family.